The Role of Principals on Teacher Performance Improvement in a Suburban School - Hamka, Hamka (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
One of the efforts to enhance the first-rate of current schooling is strengthening college principals. It is because the fundamental is the using pressure for the capacity of college resources, especially teachers, college staff, and students. In addition to having know-how and capabilities in his supervisory work, a manager's fundamental additionally calls for positive supervision strategies in sporting out his supervisory duties. This study aims to determine principals' roles and strategies in improving teacher performance. This research uses a descriptive qualitative with interviews, observation, and documentation as data collection methods. The data analysis is triangulation, negative case analysis, reference materials, and member checks. The results indicate that the role of the principal is a supervisor, consultant, group leader, and motivator. Thus, the principal must always strive to improve his leadership to carry out his function as the head of the madrasa, either by participating in scientific training activities or organizing teachers and principals. In addition, the researcher suggests that the following research should focus more on managing the principal in the decision-making process in creating comfortable conditions for the school community.